Analysis of free and forced convections in the flow of radiative viscous fluid with oxytactic microorganisms - Bilal, S.; Ullah, Asad; Shah, Imtiaz Ali; Asjad, Muhammad Imran; Almusawa, Musawa Yahya; Eldin, Sayed M. (Frontiers in Materials, 2023)
The prime intend behind current effort is to explicate flow attributes of magnetically influenced Newtonian fluid toward stretchable sheet under novel physical impact of variable molecular diffusivity and oxytactic microorganisms. In addition, modified Fourier/and Fick’s laws are implemented to examine change in temperature and concentration distributions in more realistic manner by accounting thermal and mass relaxation parameters in the flow. The obtained PDEs are reduced into the nonlinear ODEs by employing similarity variables. Due to complexity of parametrically based differential equations numerical scheme based on finite differencing approach is implemented via MATLAB built in routine renowned as BVP4C. Flow controlling parameters effects on associated distribution is evaluated through graphs and tables. Subsequently, influence of flow controlling parameters on associated distributions is revealed through pictures. Additionally, the quantities like heat and mass fluxes along with density of motile microorganisms are also illustrated. From the thorough analysis of current investigation, it is reported that by uplifting magnitudes of concentration and thermal relaxation parameters depreciation in associated heat and mass/transfer rate arises. In addition, it is also reported that with increment in magnetic field, buoyancy ratio, bio convection parameters and Rayleigh number skin friction depreciates while the behavior is quite opposite in case of stretching ratio parameter and mixed convection parameter. The authors have hoped that this work will provide an exemplary analysis on researchers performing studies in this direction. Furthermore, the current document contains novel physical aspects like variable molecular diffusivity, oxytactic microorganisms, modified Fourier and Fick's law which are not yet been considered simultaneously in the existing literature.